TRAUMA EMOSIONAL TOKOH UTAMA DALAM RELASI ROMANTIS: KAJIAN PSIKOLOGI SASTRA PADA NOVEL KUKIRA KAU OBAT, TERNYATA PATAH HATI TERHEBAT KARYA ADE RIMA MIRANTI - Emia Teta Br Bukit; Dwi Leoni, Tessa; Musliha; Irawan, Dody; Lolita, Asri; Zaitun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the emotional trauma responses and recovery process of the main character in a romantic relationship in the novel Kukira Kau Obat, Ternyata Patah Hati Terhebat by Ade Rima Miranti. This study employed a qualitative approach with a descriptive research design. The main research instrument was the researcher herself, supported by data analysis guidelines. The research data consisted of words, phrases, sentences, and narratives that describe the feelings, thoughts, attitudes, and behaviors of the main character. The data source was the novel Kukira Kau Obat, Ternyata Patah Hati Terhebat, published by Gradien Mediatama in 2024. Data were collected through reading, observation, and note-taking techniques. The data were analyzed through data reduction, data presentation, and conclusion drawing based on Judith Herman’s trauma theory. The results of the study revealed that the emotional trauma responses experienced by the main character included hyperarousal, intrusion, and constriction, with intrusion being the most dominant response. The recovery process consisted of three stages: safety, remembrance and mourning, and reconnection, with remembrance and mourning being the most dominant stage. These findings indicate that the main character’s recovery process occurred through efforts to establish a sense of safety, accept loss, restore self-worth, and rebuild connections with life.